the affirmative actions in brazilian university education: an analysis of the quinquennium 2012-2017 - Fiori, Taís Dayane (Revista Hipótese, 2019)
This article views demonstrate advances of affirmative actions in Brazilian university education in the quinquennium 2012 to 2017, period of important conquests, specially by the promulgation of the “Quotas’ Law”. A historical rescue about the theme was accomplished in worldwide level besides the first Brazilian actions in educational and labor ambit until the Quotas’ Law adventment and the inclusion of the quotas in São Paulo public universities, in order to understand the genesis of affirmative actions policies, its extends and current coverage what can contribute to studies that search the improvement of historically underprivileged groups access to the university education.
Keywords: Affirmative actions; Quotas’ Law; University education